Commerce transfrontelier et integration regionale en Afrique Centrale: cas des produits forestiers non-ligneux - Ndoye, O.; Ruíz Pérez, M. (1999)
In Central Africa, non-timber forest products (NTFP) are traded between Cameroon and neighbouring countries. kola nut (Cola acuminata) is traded between Cameroon, Nigeria and the Central African Republic. Wild mango (Irvingia gabonensis) is traded between Cameroon, Gabon and Equatorial Guinea. Okok (Gnetum africanum) is traded between Cameroon and Nigeria. As for bush butter tree (Dacryodes edulis), there is some trade between Cameroon, Gabon and Congo. Transborder trade of NTFP is based on linguistic, cultural, environmental and monetary complementarities of the countries involved. This survey shows that the quantity of NTFP sold on export markets in the wet tropical forest zone of Cameroon is quite significant, and their value is assessed at 3.099 million French francs in 1995 and 5.033 million in 1996. This gives an indication of the importance of transborder trade between Cameroon and its neighbour countries, and the need to better assess the role of NTFP in diversification of exports. Profit margins of traders are higher for bush butter than for other NTFP. Main markets for bush butter fruit are New-Bell (Douala) and Mfoundi (Yaounde), where traders' margins are higher than the SMIG (guaranteed minimum wage). In addition, the survey shows that the merchants selling wild mango kernels in Abang-Minko border market (Gabon border) in 1995 and 1996 and in Kye-Ossi border market (Equatorial Guinea border) in 1996 also earned margins higher than the SMIG. Transportation is the highest cost in NTFP marketing, especially for markets close to borders. A better harmonisation of economic policies and improvement of infrastructure could increase mobility of goods and people, and foster regional integration in Central Africa.